Functional connectivity within and between intrinsic brain networks correlates with trait mind wandering. (August 2017) - Godwin, Christine A.; Hunter, Michael A.; Bezdek, Matthew A.; Lieberman, Gregory; Elkin-Frankston, Seth; Romero, Victoria L.; Witkiewitz, Katie; Clark, Vincent P.; Schumacher, Eric H.
Abstract: Individual differences across a variety of cognitive processes are functionally associated with individual differences in intrinsic networks such as the default mode network (DMN). The extent to which these networks correlate or anticorrelate has been associated with performance in a variety of circumstances. Despite the established role of the DMN in mind wandering processes, little research has investigated how large-scale brain networks at rest relate to mind wandering tendencies outside the laboratory. Here we examine the extent to which the DMN, along with the dorsal attention network (DAN) and frontoparietal control network (FPCN) correlate with the tendency to mind wander in daily life. Participants completed the Mind Wandering Questionnaire and a 5-min resting state fMRI scan. In addition, participants completed measures of executive function, fluid intelligence, and creativity. We observed significant positive correlations between trait mind wandering and 1) increased DMN connectivity at rest and 2) increased connectivity between the DMN and FPCN at rest. Lastly, we found significant positive correlations between trait mind wandering and fluid intelligence (Ravens) and creativity (Remote Associates Task). We interpret these findings within the context of current theories of mind wandering and executive function and discuss the possibility that certain instances of mind wandering may not be inherently harmful. Due to the controversial nature of global signal regression (GSReg) in functional connectivity analyses, we performed our analyses with and without GSReg and contrast the results from each set of analyses. Highlights: Resting state functional connectivity was examined in several intrinsic networks. Connectivity between the DMN and FPCN positively correlated with trait mind wandering. Connectivity within the DMN positively correlated with trait mind wandering. Trait mind wandering positively correlated with fluid intelligence and creativity.